Kajian Pengaruh Sekolah Adiwiyata Dalam Meningkatkan Kualitas Pendidikan - Aprianto; Nopriawan Berkat Asi; Jackson Pasini Mairing; Maya Erliza Anggraeni; Revianti Coendraad; Eriawaty; Lola Cassiophea; Whendy Trissan (Jurnal Ilmiah Kanderang Tingang, 2023)
This study aims to study the influence of the adiwiyata school movement on the quality of education. This type of research is experimental research with a quantitative approach. This study compares environmental literacy, attitudes towards the environment, reading literacy, and numeracy literacy between adiwiyata schools and schools with adiwiyata potential. Data in the form of numbers obtained from reading literacy tests, numeracy literacy tests, environmental literacy tests and environmental care attitude questionnaires. The population in this study were 9 junior high schools with details of 3 schools that had achieved adiwiyata in the last five years and 6 public junior high schools with adiwiyata potential in Jekan Raya sub-district. Samples were taken randomly, where one school represented an adiwiyata school and one school represented adiwiyata potential. The sampling technique uses cluster random sampling (clustered random sampling). The result is that SMPN 9 Palangka Raya represents an adiwiyata school and SMPN 11 represents adiwiyata potential. The instruments used to collect data in this study were in the form of a questionnaire (questionnaire), objective test items, and interview guidelines and observation guidelines as supporting instruments. Data were analyzed statistically using Minitab software. The results of the study showed (1) the environmental literacy of SMPN 11 students was higher than that of SMPN 9 with a 95% confidence level, which means that there was no influence of adiwiyata schools on environmental literacy. (2) Students' attitudes towards the environment at SMPN 11 are better than SMPN 11 with a 95% confidence level, which means that there is no influence from Adiwiyata schools on students' attitudes towards the environment. (3) The reading literacy of SMPN 9 students is the same as SMPN 11 with a 95% confidence level, which means that there is no influence of adiwiyata schools on reading literacy. (4) The numeracy literacy of SMPN 11 students is more than SMPN 9 with a 95% confidence level, which means that there is no influence of adiwiyata schools on environmental literacy in numeracy. (5) Student achievement in both schools in the last five years is relatively the same.